2016
DOI: 10.18203/2320-6012.ijrms20160083
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analytical five months study of aortic arch abnormalities

Abstract: INTRODUCTION Aortic arch abnormalities include congenital anomalies and acquired pathologies .Variant anatomy of the aortic arch occurs when there is failure of normal aortic development. It results in a number of heterogenous anomalies of the aorta and its branch vessels. Radiological investigations are important for diagnosis of these conditions. Many of aortic arch anomalies are asymptomatic lesions. But some of these anomalies are symptomatic and need to be treated. Radiological appearances should be famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Rea G et. al, reported this variation in o.5% in his study, [17] it is 0.4% according to Nellaiappan Chellaiah, [18] while some of the authors presented as case reports. In the current study it was found in 5 cases (1%) of the study population.…”
Section: Resultsmentioning
confidence: 94%
“…Rea G et. al, reported this variation in o.5% in his study, [17] it is 0.4% according to Nellaiappan Chellaiah, [18] while some of the authors presented as case reports. In the current study it was found in 5 cases (1%) of the study population.…”
Section: Resultsmentioning
confidence: 94%